Daily Relaxation Microbreaks and Work Engagement: The Mediating Role of Employee Well-Being - Irma Suryani; Nurhalis Nurhalis; Jasman J Ma’ruf (Management Institute Faculty of Economics Universitas Andalas, 2026)
Micro-breaks have received increasing attention as a workplace recovery strategy that may help employees maintain positive psychological conditions and sustain work-related outcomes. This study examines the relationship between relaxation microbreaks and employee work engagement, with employee well-being as a mediating variable. Data were collected using repeated daily observations from employees over five consecutive workdays. A total of 220 observation episodes were obtained from 22 employees working in financial service institutions in Aceh, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that relaxation microbreaks were positively associated with employee well-being and work engagement. Employee well-being was also positively associated with work engagement and significantly mediated the relationship between relaxation microbreaks and work engagement. These results suggest that brief relaxation activities during work may contribute to employees’ psychological recovery and foster stronger engagement by improving well-being. This study contributes to the employee recovery and engagement literature by highlighting the importance of microbreaks as a simple workplace practice that supports positive psychological and work-related outcomes. The findings also have practical implications for organizations, encouraging brief recovery opportunities during work to enhance employee well-being and engagement. Keywords: micro-breaks; employee well-being; work engagement; repeated daily observations; PLS-SEM